ERGOFISHBOX: INOVASI KOTAK PENYIMPANAN IKAN BERBASIS ANTROPOMETRI UNTUK KESEJAHTERAAN NELAYAN TRADISIONAL KEPULAUAN RIAU - Maulidina, Siti Nur; Wibowo, Sadiq Ardo; Rahman, Taufiq; Bakang, Maria Clarita Tuto (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
The capture fisheries sector plays a crucial role in supporting food security and the Indonesian economy, particularly in the Riau Islands region. Traditional fishermen hold a pivotal position in the post-harvest chain of capture fisheries. However, traditional fishermen still face various challenges, one of which relates to non-ergonomic working conditions when storing fish catches. Currently, traditional fishermen use makeshift fish storage boxes without considering ergonomic and anthropometric aspects. Non-ergonomic storage boxes can cause health problems such as back pain, muscle injuries, and excessive fatigue among fishermen. This condition can negatively impact fishermen's productivity and quality of life. This research is essential to develop an ergonomic fish storage box design that aligns with the anthropometric characteristics of traditional fishermen. With ergonomic equipment, it is expected to enhance fishermen's comfort and occupational safety while minimizing health risks associated with work activities. Furthermore, ergonomic equipment can also improve fishermen's productivity and work efficiency in storing fish catches. The aim of this research is to design ergonomic equipment for traditional fishermen that corresponds to anthropometric characteristics, thereby facilitating and enhancing comfort and occupational safety for traditional fishermen. This research will employ an anthropometric approach as the foundation for designing ergonomic equipment for traditional fishermen. Data collection will involve anthropometric measurements of traditional fishermen using a sample of fishermen as respondents. Body dimension measurements will be conducted to obtain static and dynamic anthropometric data. Based on the anthropometric data, a prototype of an ergonomic fish storage device will be developed.